Use of Newer Anticonvulsants for the Treatment of Status Epilepticus. Issue 3 (11th March 2019) - Farrokh, Salia; Bon, John; Erdman, Michael; Tesoro, Eljim
Abstract : Status epilepticus (SE) has a high mortality rate and is one of the most common neurologic emergencies. Fast progression of this neurologic emergency and lack of response to traditional antiepileptic drugs (AEDs) in most cases has challenged clinicians to use new agents. This article evaluates the efficacy and safety of AEDs released to the market after 2000 for SE, refractory status epilepticus (RSE), and super‐refractory status epilepticus (SRSE). The PubMed database was searched for clinical trials published between January 2000 and July 2018 using the search terms status epilepticus, refractory status epilepticus, super refractory status epilepticus, brivaracetam, clobazam, cannabidiol, eslicarbazepine, lacosamide, perampanel, rufinamide, stiripentol, and zonisamide . Trials that evaluated these agents in adults with SE, RSE, and SRSE were included. Brivaracetam use was identified in two retrospective reviews with success rates of 27% and 57%. One unsuccessful case report of cannabidiol use in SE was found. Four clobazam studies were identified in SE and RSE with success rates ranging from 25–100%. No evidence for the use of eslicarbazepine and zonisamide was found. Using the search terms for lacosamide identified 38 articles: 1 systematic review, 5 prospective studies, 15 retrospective reviews, and 17 case reports. Success rates and dosing varied, but studies that included focal or partial types of SE showed higher success rates. Five articles were identified regarding perampanel use in this setting. Three were retrospective reviews with success rates ranging from 17–60%, and two were case reports. Only one case report regarding the use of rufinamide was found; rufinamide titrated up to 4.4 mg/day allowed discontinuation of barbiturate and clobazam. One case report and two case series of stiripentol were found with reported efficacy between 60% and 100% in SRSE. Evidence is currently insufficient to support the use of these agents in this setting.